DETERMINASI SOSIAL LINGKUNGAN KERJA DAN EPIDEMIOLOGI MANAJERIAL: TINJAUAN LITERATUR MODEL STRUKTURAL KEPEMIMPINAN PELAYANAN DAN BUDAYA KERJA TERHADAP KOMITMEN PERAWAT MELALUI MEDIASI KEPUASAN KERJA DAN MODERASI KEPERCAYAAN PADA LEMBAGA PADA RSUD PROVINSI - I Putu Artawan Prayoga; Yuly Peristiowati (Bajang Institute, 2026)
Background: Nurse commitment is a fundamental pillar in maintaining the quality of healthcare services at RSUD Provinsi NTB. However, workplace dynamics and managerial challenges often hinder the retention of medical staff loyalty. Objective: This study aims to theoretically analyze the influence of a structural model of servant leadership and work culture on nurse commitment, examining the role of job satisfaction as a mediating variable and institutional trust as a moderating variable. Method: This study employs a Systematic Literature Review (SLR) method. Literature searches were conducted across Scopus, Google Scholar, and ScienceDirect databases spanning 2014-2024. Article selection followed strict inclusion and exclusion criteria focusing on organizational behavior studies in the healthcare sector. Results: Findings indicate that servant leadership and a positive work culture significantly enhance nurse commitment. Job satisfaction is proven to mediate this relationship, confirming that fulfilling nurses' emotional and professional needs is a prerequisite for commitment. Furthermore, institutional trust is identified as a key moderator that strengthens the impact of satisfaction on commitment; a crisis of trust in management can undermine the effectiveness of organizational policies. Conclusion: The integration of servant leadership styles and institutional transparency is essential for building sustainable nurse commitment at RSUD Provinsi NTB.